1969
DOI: 10.1063/1.1657506
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structure and Exchange Interactions in Cubic Gadolinium Compounds

Abstract: The two groups of metallic compounds Gd3+X3− (X=N, P, As, Sb, Bi) and Gd3+Z2− (Z=S, Se, Te) have the rocksalt structure and except for ferromagnetic GdN they are antiferromagnetic. Powder neutron diffraction measurements on GdS, GdSe, GdSb, and GdBi show them to have order of the second kind. The exchange interactions are discussed on the basis of the magnetic structure and susceptibility measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 6 publications
3
31
0
Order By: Relevance
“…Among the RE nitrides, crystalline gadolinium nitride has been the most thoroughly studied since the late 60s. Historically, there have been conflicting and contradictory results on its magnetic [3][4][5][6] and electrical [7,8] properties. This was partially due to poor sample preparation techniques for the deposition of defect and impurity free gadolinium nitride films with the correct stoichiometry.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the RE nitrides, crystalline gadolinium nitride has been the most thoroughly studied since the late 60s. Historically, there have been conflicting and contradictory results on its magnetic [3][4][5][6] and electrical [7,8] properties. This was partially due to poor sample preparation techniques for the deposition of defect and impurity free gadolinium nitride films with the correct stoichiometry.…”
Section: Introductionmentioning
confidence: 98%
“…This was partially due to poor sample preparation techniques for the deposition of defect and impurity free gadolinium nitride films with the correct stoichiometry. However, crystalline gadolinium nitride has now been widely accepted to be ferromagnetic [3][4][5][6] and semiconducting [9][10][11]. Gadolinium nitride has a Curie temperature of $70 K and a large magnetic moment of 7 Bohr magnetons (m B ) per Gd 3 þ [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…From the Curie law for the nuclear magnetic moment, the relation B n p Am N p1=T is given, where A is the hyperfine coupling constant and m N the nuclear moment [7]. 1) and (2). The agreement between the experimental data and the calculated results is quite good.…”
Section: Article In Pressmentioning
confidence: 59%
“…From neutron diffraction studies for GdSb and GdBi powder, McGuire et al suggested that they have a type-II antiferromagnetic structure below the N! eel temperature and the magnetic moments lie in the ð1 1 1Þ plane in zero magnetic field [1,2]. In general, it is difficult to determine the magnetic structure of Gd-compounds using conventional neutron diffraction experiments, because the absorption cross-section of neutrons is very large for Gd.…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between experiment and calculations made by Van Vleck and Frank [19] on the effective magneton number of the rare-earth ions was regarded as one of the most successful applications of quantum mechanics to magnetism [20]. The surge in the study of rare-earth compounds in the 1960s was mainly motivated by a search for new ferromagnetic semiconductors [21][22][23][24][25][26][27]. Researchers began realizing that it was too complicated to interpret the experimental results if crystal distortions or impurities were considered.…”
Section: Early Experiments and Theoretical Studiesmentioning
confidence: 99%